Nutritional support in severe burns - Oviedo Assunção, Tayná; Lipovestky, Fernando (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Burns are partial or total skin lesions, classified according to their etiology into thermal, electrical, chemical and radiation, which cause profound physiological, metabolic, hormonal and immunological alterations. A bibliographic review has been carried out on which nutrients intervene in the viability of the recovery process in patients with severe burns, with the aim of investigating which dietary regimens are prescribed in relation to their dietary behavior. The results of this review suggest adequate nutritional support, and generating a positive impact on recovery. The choice of route of administration depends on the patient’s situation, but it is important to calculate the amount of energy, protein, carbohydrates, lipids, vitamins and minerals. Objectives: The aim of this review is to analyze the current state of knowledge on nutritional support in severe burn patients, metabolic and catabolic changes and dietary strategies. Material and methods: Bibliographic searches of scientific articles in English and Spanish journals were performed through the US National Library of Medicine (PubMed), the Online Medical Literature Analysis and Retrieval System (Medline), the Virtual Health Library (VHL), the Scientific Electronic Virtual Library (SciELO) and electronic searches in journals and books. Data collection was conducted in November and December 2022